The Appropriate forecasting models and dependence measurement : real estate sector stock and Shenzhen index in people’s Republic of China - Lili Zhou (Chiang Mai : Graduate School, Chiang Mai University, 2014)
This paper mainly has two purposes. On the one hand, it aims to find the appropriate models for forecasting the Real Estate Sector Stock and Shenzhen Index in People’s Republic of China, respectively. On the other hand, this paper will analyze the dependence measures between these two kinds of stock indexes in China. The linear method and nonlinear method was introduced for seeking the appropriate models for each stock index. And the empirical copula method was implied to examine the dependence measures between these two indexes. The results vi are: Firstly, the Autoregressive-linear model (AR-linear Model) fits for forecasting the Real Estate Sector Stock and Shenzhen Index over the period of 2006 to 2012. Secondly, based on the empirical copula approach, the dependence measures between returns in percentage of Real Estate Sector Stock and Shenzhen Index is very strong